'No Nation of Experts': Kustom Tattooing and the Middle-Class Body in Post-Authoritarian Indonesia. Issue 2 (15th March 2017) - Hegarty, Benjamin
Abstract : Tattooing among young middle-class people in Indonesia has increased noticeably since the late 2000s. I draw on ethnographic research in tattoo studios alongside interviews and magazine sources to locate the style known as kustom within its social and cultural context. I describe how kustom tattooing is the product of patterns of consumption centred on the body, drawing resources from a globalised, mass media-saturated environment. Indeed, consumers describe it as an important avenue for self-expression. By contrast, tattooists and those inside the scene describe kustom as a way of transcending geographical markers of identity: to be 'anything and everything'. This article explores this tension between self-expression and the political aims of kustom . Kustom tattooing is also novel by virtue of its absolute emphasis on 'no expertise'. It thus exposes a space where the stress on expertise and self-improvement, which characterises middle-class cultures in post-authoritarian Indonesia, gives way to creative and hybrid articulations of identity.